Pengujian Blackbox Testing terhadap Simbs:Website Travel Booking : Penelitian - Danti Rosdianti; Raafi Syarahil Azhar; Rahmat Hidayat; Sandi Rosandi; Subhanjaya Angga Atmaja (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
In developing travel booking applications, errors in the system can cause major losses for users and service providers. For users, if the application experiences problems then the process of ordering tickets or travel services will be hampered, causing inconvenience and even potentially losing the opportunity to travel. Meanwhile, for service providers (travel companies), application failure in processing orders quickly and accurately can reduce the level of consumer trust and impact the company's reputation. The testing method used in this application is the black box method with boundary value analysis and equivalence partition techniques. This technique is used to measure the quality of the application by testing the validity of the input data, especially in important columns such as travel date, number of passengers and destination. Testing is carried out by identifying the upper and lower limit values for each input, to ensure that there are no errors stored in the database. Testing is focused on the travel booking form, going through certain stages that have been determined for each input column. The results of this test can be used as input to improve application reliability and performance. Thus, the travel booking application being developed is expected to be able to provide a booking experience that is fast, precise and meets user expectations.